2005
DOI: 10.1037/0882-7974.20.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical linear modeling analyses of the NEO-PI-R Scales in the Baltimore Longitudinal Study of Aging.

Abstract: We examined age trends in the five factors and 30 facets assessed by the Revised NEO Personality Inventory in Baltimore Longitudinal Study of Aging data (N = 1,944; 5,027 assessments) collected between 1989 and 2004. Consistent with cross-sectional results, Hierarchical Linear Modeling analyses showed gradual personality changes in adulthood: a decline up to age 80 in Neuroticism, stability and then decline in Extraversion, decline in Openness, increase in Agreeableness, and increase up to age 70 in Conscienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
486
6
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 461 publications
(574 citation statements)
references
References 75 publications
74
486
6
8
Order By: Relevance
“…Recent reports find no evidence for gender differences in rates of mean level personality changes across the lifespan (Roberts et al, 2006;Terracciano et al, 2005); thus one would not expect the relative differences between men and women's mean levels of these traits to change in older age. A supplementary aim was to test whether some previously reported findings at the level of more specific components of FFM domains would be replicable.…”
mentioning
confidence: 91%
“…Recent reports find no evidence for gender differences in rates of mean level personality changes across the lifespan (Roberts et al, 2006;Terracciano et al, 2005); thus one would not expect the relative differences between men and women's mean levels of these traits to change in older age. A supplementary aim was to test whether some previously reported findings at the level of more specific components of FFM domains would be replicable.…”
mentioning
confidence: 91%
“…The development of Openness has shown a curvilinear pattern, increasing in early adulthood and decreasing in old age (Roberts et al, 2006; cf. for younger individuals, Lüdtke et al, in press, and for older individuals, Terracciano et al, 2005).…”
Section: Distinguishing Types Of Personality Changesmentioning
confidence: 99%
“…Most studies show an increase in Emotional Stability with increasing age (Bleidorn et al, 2009;Lucas & Donnellan, 2009;Lüdtke, Roberts, Trautwein, & Nagy, in press;Neyer & Asendorpf, 2001;Neyer & Lehnart, 2007;Roberts et al, 2006;Soto, John, Gosling, & Potter, 2011;Terracciano, McCrae, Brant, & Costa, 2005), an increase in Conscientiousness (Lucas & Donnellan, 2009;Lüdtke et al, in press;Neyer & Asendorpf, 2001;Neyer & Lehnart, 2007;Roberts et al, 2006;Soto et al, 2011) in some studies followed by a decrease in advanced old age (Terracciano et al, 2005), and stability or an increase in Agreeableness (Bleidorn et al, 2009;Lucas & Donnellan, 2009;Lüdtke et al, in press;Neyer & Asendorpf, 2001;Neyer & Lehnart, 2007;Roberts et al, 2006, Soto et al, 2011Terracciano et al, 2005). There have been mixed results for Extraversion, with the facet Social Vitality decreasing and the facet Social Dominance increasing with age (Roberts et al, 2006).…”
Section: Distinguishing Types Of Personality Changesmentioning
confidence: 99%
“…Cross-sectional and longitudinal research in the field of personality development has shown that personality traits can change over longer time periods and continue to change in adulthood into old age (Allemand, Zimprich, & Hertzog, 2007;Lucas & Donnellan, 2011;Roberts, Walton, & Viechtbauer, 2006;Terracciano, McCrae, Brant, & Costa, 2005). In general, personality trait changes are small in magnitude with respect to specific age periods.…”
Section: Introductionmentioning
confidence: 99%